Voltammetric Determination of Cadmium in Infant Mllk - Haznan, Hashim (PPSP, Universiti Sains Malaysia, 2007)
Among the various environmental pollutants, heavy metals like cadmium was considered the most important due to high stability for bioaccumulation they were extremely dangerous for all biological organisms and especially for humans. This is a great importance to analyze and quantify this toxic agent in the environment. Various methods have been done such as atomic absorption spectrometry (AAS), atomic emission spectrometry (AES) in determination of cadmium in matrix. Often these techniques require complex sample preparation and expensive instrumentation. In contrast, voltammetric methods particularly anodic stripping voltammetric (ASV) had some advantages such as little or no sample pretreatment is required, detection limit is as low as 1 o-10 M and low cost instrumentation. For this work, cadmium was studied in various brand of infant milk. Besides, aim of this work was to improve anodic stripping voltammetric (ASV) method for cadmium detection by optimizing voltammetric condition (pH) and voltammetric parameters such as initial potential (Ei), final potential (Er), scan rate (v), deposition potential (Eacc), deposition time (tacc). and equilibration time (feq) in ASV. The samples preparation was done by extraction using acid digestion and filtration using filter paper. The samples were analyzed under optimized voltammetric condition and parameters. Cadmium was not detected in any of studied under this project work.